The Influence of Product Quality and Digital Marketing on Customer Loyalty in Coffee Bean Products at Titik Tuju Kediri - Rahmadi, Afif Nur; Sudarmiatin; Wardana, Ludi Whisnu (RISK : Jurnal Riset Bisnis dan Ekonomi, 2023)
This research aims to determine the influence of product quality and digital marketing partially and simultaneously on customer loyalty to coffee bean products at Point Tuju Kediri. The population in this study were customers who bought coffee bean products, with a sample of 96 respondents. The sampling technique is to use Non-Probability Sampling. This research focuses on marketing issues, especially to determine how much influence product quality and digital marketing have on loyal customers. Based on the results of the study And analysis, we can conclude that Product quality significantly affects customer loyalty to coffee bean products in Point Tuju Kediri, and digital marketing partially has no effect on customer loyalty. Product quality and digital marketing simultaneously significantly affect customer loyalty to coffee bean products in Point Tuju Kediri.